MEMBANGUN PARADIGMA TAFSIR SEMANTIK : REKONTRUKSI METODE TOSHIHIKO IZUTSU DALAM STUDI AL QUR’AN KONTEMPORER - Humrotus Safataeni; Muhammad Akmal Widad; Sifa Faujiah; Muhammad Fadli; Andi Rosa (Adisam Publisher, 2025)
This study discusses the reconstruction of the semantic interpretation method of toshihiko izutsu in order to build a paradigm of interpretation of the Qur'an that is so relevant to the needs of contemporary thinking. The semantic method of izuts is also seen as a very important approach because it is able to reveal the network of interrelated meanings in the language structure in the Qur'an, as well as showing the Qur'an's perspective on reality. However, in this application, it is still very limited to linguistic and philosophical analysis. So far, the izutsu method has also been more focused on language only, while the social situation, human problems are less considered. Therefore, this study tries to develop this method so that it can be used to understand the Qur'an more broadly and in accordance with life today. This study also discusses a new way to more easily understand the Qur'an through a method made by Toshihiko Izutsu, which according to Izutsu, the words contained in the Qur'an are interconnected. Therefore, they cannot be understood in isolation. Because this research is seen from how the method works and also how to improve it so that it is more suitable for use today.